EXAMINING OF MODEL ELICITING ACTIVITIES DEVELOPED BY MATHEMATICS STUDENT TEACHERS - Ayse Tekin Dede; Çaglar Naci Hidiroglu; Esra Bukova Guzel (Journal on Mathematics Education, 2017)
The purpose of this study is to examine the model eliciting activities developed by the mathematics student teachers in the context of the principles of the model eliciting activities. The participants of the study conducted as a case study design were twenty one mathematics student teachers working on seven groups. The data collection tools were the developed model eliciting activities and semi-structured interviews. The model eliciting activities and the transcriptions of the interviews were deeply analyzed based on the principles. The results showed that while one group’s activity was not a model eliciting activity, the ones of two groups were appropriate to the all principles. Other model eliciting activities were completely or partly appropriate to the principles. It was seen that the reality and model construction principles were binding role in developing these activities. The self-assessment and construct documentation principles were directly related to each other. The construct share ability and reusability, and effective prototype principles were the principles which were associated with the others and could be elicited effectively by tracking future implementations.